ARCHITECTURE TYPES AND FORMING ELEMENTS OF NUAONE TRADITIONAL TRADITIONAL HOUSE, ENDE DISTRICT - Alfons Mbuu; DVX.Dedy Kurniawan (Sean Institute, 2022)
Nuaone is one of the traditional settlement areas in Woloara Village, Kelimutu District, Ende Regency, NTT Province, which still adheres to the beliefs of their ancestors from generation to generation. Traditions and culture formed in the architecture of traditional houses in the traditional settlements of Nuaone still maintain local wisdom, to this day they still protect their traditional houses from all changes. The aim of the study is to identify the values of the teachings of belief in the traditional Nuaone traditional house architecture. The research method used is descriptive qualitative and hermeneutic with a sample of 10 elements forming the traditional Nuaone house which were selected by simple random sampling. Data collection by means of field observations and interviews. Descriptive analysis of the function, form and structure of the traditional Nuaone traditional house, to find out the implementation of cultural values in the traditional Nuaone traditional house. The results of this study indicate that the architecture of traditional Nuaone traditional houses is formed based on philosophical concepts, namely the concept of the trajectory of the solar system orbit, the concept of Mount Lepmbusu, the concept of building houses and their elements oriented to cosmological values based on belief systems and local traditions.